Assigning vibrational spectra of ferryl-oxo intermediates of cytochrome c oxidase by periodic orbits and molecular dynamics - Farantos, Stavros C.; Varotsis, Constantinos; Daskalakis, Vangelis (My University, 2008)
Complexity is inherent in biological molecules not only because of the large number of atoms but also because of their nonlinear interactions responsible for chaotic behaviours, localized motions, and bifurcation phenomena. Thus, versatile spectroscopic techniques have been invented to achieve temporal and spacial resolution to minimize the uncertainties in assigning the spectra of complex molecules. Can we associate spectral lines to specific chemical bonds or species in a large molecule? Can energy stay localized in a bond for a substantial period of time to leave its spectroscopic signature? These longstanding problems are investigated by studying the resonance Raman spectra of ferryl-oxo intermediates of cytochrome c oxidase. The difference spectra of isotopically substituted ferryl oxygen (16O minus 18O) in the cytochrome c oxidase recorded in several laboratories show one or two prominent positive peaks which have not been completely elucidated yet. By applying the hierarchical methods of nonlinear mechanics, and particularly the study of periodic orbits in the active site of the enzyme, in conjunction with molecular dynamics calculations of larger systems which include the embraced active site by the protein and selected protonated/deprotonated conformations of amino acids, we translate the spectral lines to molecular motions. It is demonstrated that for the active site stable periodic orbits exist for a substantial energy range. Families of periodic orbits which are associated with the vibrations of FeIV=O bond mark the regions of phase space where nearby trajectories remain localized, as well as assign the spectral bands of the active site in the protein matrix. We demonstrate that proton movement adjacent to active site, which occurs during the P → F transition, can lead to significant perturbations of the Fe IV=O isotopic difference vibrational spectra in cytochrome c oxidase, without a change in oxidation state of the metal sites. This finding links spectroscopic characteristics to protonation events occurring during enzymatic turnover
Keywords: Molecules; Atoms; Chemical bonds; Chlorine compounds; Dynamics; Molecular dynamics; Molecular spectroscopy; Nonmetals; Oxygen; Quantum chemistry; Heme; Energy